Host cell binding of the flagellar tip protein of Campylobacter jejuni. (24th January 2017) - Freitag, Claudia M.; Strijbis, Karin; van Putten, Jos P.M.
Abstract: Flagella are nanofibers that drive bacterial movement. The filaments are generally composed of thousands of tightly packed flagellin subunits with a terminal cap protein, named FliD. Here, we report that the FliD protein of the bacterial pathogen Campylobacter jejuni binds to host cells. Live‐cell imaging and confocal microscopy showed initial contact of the bacteria with epithelial cells via the flagella tip. Recombinant FliD protein bound to the surface of intestinal epithelial cells in a dose‐dependent fashion. Search for the FliD binding site on the host cell using cells with defined glycosylation defects indicated glycosaminoglycans as a putative target. Heparinase treatment of wild type cells and an excess of soluble heparin abolished FliD binding. Binding assays showed direct and specific binding of FliD to heparin. Addition of an excess of purified FliD or heparin reduced the attachment of viable C . jejuni to the host cells. The host cell binding domain of FliD was mapped to the central region of the protein. Overall, our results indicate that the C . jejuni flagellar tip protein FliD acts as an attachment factor that interacts with cell surface heparan sulfate glycosaminoglycan receptors.